2023
DOI: 10.1007/s12079-023-00733-2
|View full text |Cite
|
Sign up to set email alerts
|

Sam68 promotes osteogenic differentiation of aortic valvular interstitial cells by TNF-α/STAT3/autophagy axis

Abstract: Calcified aortic valve disease (CAVD) is a major non‐rheumatic heart valve disease in the world, with a high mortality rate and without suitable pharmaceutical therapy due to its complex mechanisms. Src‐associated in mitosis 68‐KD (Sam68), an RNA binding protein, has been reported as a signaling adaptor in numerous signaling pathways (Huot in Mol Cell Biol, 29(7), 1933‐1943, 2009), particularly in inflammatory signaling pathways. The effects of Sam68 on the osteogenic differentiation process of hVICs and its r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…Although numerous of the factors contributing to valve calcification are understood, the role of autophagy within this process remains elusive ( 18 , 34 ). This significant research gap warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although numerous of the factors contributing to valve calcification are understood, the role of autophagy within this process remains elusive ( 18 , 34 ). This significant research gap warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous studies have highlighted the key role of the RNA-binding protein Sam68 in driving human valve interstitial cell osteogenic differentiation via the STAT3 signaling pathway and autophagic flux regulation ( 18 ). In addition, autophagy upregulation has been observed in the calcified tissues of patients, showing that autophagy plays compensatory and pro-survival roles in this disease ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…The initial stage of is CAVD pathological process characterized by lesion development which is similar to that of atherosclerosis, such as endothelial injury, lipid infiltration, and inflammatory response ( 72 ). Nordquist et al showed that in the mouse model of heart valve endothelial cell injury, positive injury response was associated with an acute increase in TGF-β1 enriched within the endothelial compartment and upregulation of CTHRC1 within the interstitium.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, changes in these genes led to osteogenic calcification ( 82 ). Additionally, upregulated Src-associated in mitosis 68-KD (Sam68) expression was found in human CAV, which coordinated with STAT3, resulting in mineral deposition and osteogenic differentiation ( 85 ) ( Figure 2A ). These results showed that SPP1-Sam68-STAT3 signaling could mediate macrophages in CAVD.…”
Section: The Association Between Spp1 and Immune Cells In Vascular Ca...mentioning
confidence: 99%